Antifungal Effect of Hydrogen Peroxide on Catalase-Producing Strains of Candida spp. - Bryan Larsen; Sandra White (Hindawi Limited, 1995)
Objective: Clinical isolates of Candida were tested for the presence of catalase and susceptibility to hydrogen peroxide.